2020
DOI: 10.1161/circep.120.008503
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of an Antibacterial Envelope for Cardiac Implantable Electronic Device Infection Prevention in the US Healthcare System From the WRAP-IT Trial

Abstract: Background - In the WRAP-IT trial, adjunctive use of an absorbable antibacterial envelope resulted in a 40% reduction of major cardiac implantable electronic device (CIED) infection without increased risk of complication in 6,983 patients undergoing CIED revision, replacement, upgrade, or initial cardiac resynchronization therapy defibrillator (CRT-D) implant. There is limited information on the cost-effectiveness of this strategy. As a pre-specified objective, we evaluated antibacterial envelope c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 43 publications
3
29
0
Order By: Relevance
“…In line with these results, a recent study from the perspective of the US healthcare system found the envelope to be costeffective in the population formed by the WRAP-IT inclusion criteria, at an upper threshold of $150 000 per QALY when compared to SOC infection prevention among patients at increased risk of infection. 37 The study also used data from the WRAP-IT trial, although it did not include PADIT score subgroups as adopted in the current model.…”
Section: Discussionmentioning
confidence: 99%
“…In line with these results, a recent study from the perspective of the US healthcare system found the envelope to be costeffective in the population formed by the WRAP-IT inclusion criteria, at an upper threshold of $150 000 per QALY when compared to SOC infection prevention among patients at increased risk of infection. 37 The study also used data from the WRAP-IT trial, although it did not include PADIT score subgroups as adopted in the current model.…”
Section: Discussionmentioning
confidence: 99%
“…Two CEAs have been conducted by clinical study investigators involved in the WRAP-IT. 45 , 46 Both analyses were based on a prior model 47 and because CEA was pre-specified for the WRAP-IT study, both analyses used prospectively collected data for patients’ quality of life (EQ-5D) and healthcare resource use, in addition to clinical endpoints. 43 One study tailored the resource use and cost inputs for the US healthcare system 45 while the second analysis presented data for three European countries (UK, Germany, and Italy).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the observed 23% reduction in HFH-related expenditures with SyncAV™-enabled CRT is notable. Assuming 7.8-and 4.2-year life expectancy of patients with CRT-D and CRT-P devices, respectively 27 , lifetime savings amount to $4,031 per CRT patient when SyncAV™ is enabled.…”
Section: Discussionmentioning
confidence: 99%